Себорейний дерматит і Malassezia spp. - Одінцова, І. В.; Дюдюн, А. Д.; Гладишев, Віталій Валентинович; Поліон, Н. М.; Odintsova, I. B.; Dyudyun, A. D.; Gladishev, V. V.; Polion, N. M. (My University, 2019)
Себорейний дерматит (СД) – хронічне захворювання шкіри, що супроводжується підвищеною продукцією шкірного сала, запаленням і лущенням на шкірі в зонах з великим вмістом сальних залоз, які називаються себорейними зонами (волосиста частина голови, обличчя, верхня частина тулуба, складки) [3, 6, 10]. СД – одне з найпоширеніших захворювань, на яке страждають до 16% населення, виникає в перші тижні життя, надалі часто загострюється в підлітковий і юнацький періоди, стаючи хронічним. На СД частіше страждають чоловіки [2]. The objective of the work was the identification of Malassezia spp. in patients with seborrheic dermatitis. Materials and methods. We observed 57 patients with seborrheic dermatitis between the ages of 18 and 57 years. The average age of patients was 27.5 years. All the patients with seborrheic dermatitis were examined by the following methods: examination of the skin, microscopic and bacteriological examination, general and biochemical blood analysis, urinalysis, and consideration of the patient’s subjective sensations. Results and its discussion. Among patients with seborrheic dermatitis, a fatty clinical form was established in 33 (57.9%), mixed in 17 (28.8%) and dry in 7 (12.3%) patients. A comprehensive microbiological examination of 57 patients with seborrheic dermatitis allowed to detect Malassezia spp. in 87.7% of patients. The disease often began during puberty. Dermatitis had a long course with frequent relapses, mainly in the autumn-winter period and due to a violation of the diet. Conclusions. The presence in 87.7% of patients Malassezia spp. confirms its role in the development and maintenance of recurrence of seborrheic dermatitis, which a doctor must consider while planning a complex treatment.
Seborrheic dermatitis and Malassezia spp.
Keywords: seborrheic dermatitis; Malassezia spp.; complex treatment